Genomics and transcriptomics yields a system-level view of the biology of the pathogen Naegleria fowleri - Herman, Emily K; Greninger, Alex; van der Giezen, Mark; Ginger, Michael L; Ramirez-Macias, Inmaculada; Miller, Haylea C; Morgan, Matthew J; Tsaousis, Anastasios D; Velle, Katrina; Vargová, Romana; Záhonová, Kristína; Najle, Sebastian Rodrigo; et al. (BMC biology, 2021)
BACKGROUND: The opportunistic pathogen Naegleria fowleri establishes infection in the human brain, killing almost invariably within 2 weeks. The amoeba performs piece-meal ingestion, or trogocytosis, of brain material causing direct tissue damage and massive inflammation. The cellular basis distinguishing N. fowleri from other Naegleria species, which are all non-pathogenic, is not known. Yet, with the geographic range of N. fowleri advancing, potentially due to climate change, understanding how this pathogen invades and kills is both important and timely. RESULTS: Here, we report an -omics approach to understanding N. fowleri biology and infection at the system level. We sequenced two new strains of N. fowleri and performed a transcriptomic analysis of low- versus high-pathogenicity N. fowleri cultured in a mouse infection model. Comparative analysis provides an in-depth assessment of encoded protein complement between strains, finding high conservation. Molecular evolutionary analyses of multiple diverse cellular systems demonstrate that the N. fowleri genome encodes a similarly complete cellular repertoire to that found in free-living N. gruberi. From transcriptomics, neither stress responses nor traits conferred from lateral gene transfer are suggested as critical for pathogenicity. By contrast, cellular systems such as proteases, lysosomal machinery, and motility, together with metabolic reprogramming and novel N. fowleri proteins, are all implicated in facilitating pathogenicity within the host. Upregulation in mouse-passaged N. fowleri of genes associated with glutamate metabolism and ammonia transport suggests adaptation to available carbon sources in the central nervous system. CONCLUSIONS: In-depth analysis of Naegleria genomes and transcriptomes provides a model of cellular systems involved in opportunistic pathogenicity, uncovering new angles to understanding the biology of a rare but highly fatal pathogen.
Keywords: Inter-strain diversity; Metabolism; Genome sequence; Protease; genomika; Cytoskeleton; Naegleria fowleri; transkriptom; Illumina; Disease Models, Animal; Mice; trogocytóza; Lysosomal; Transcriptome; Trogocytosis; modely nemocí na zvířatech; zvířata; Genomics; myši; RNA-Seq; Neuropathogenic; Animals